Analysis of risk factors for mental health problems of inpatients with chronic liver disease and nursing strategies: A single center descriptive study. Issue 12 (11th November 2021) - Qin, Zhu; Shen, Yannan; Wu, Yuanhao; Tang, Haicheng; Zhang, Lin
Abstract: The number of patients with chronic liver disease (CLD) is large. The social and economic burdens due to CLD have increased. The mental health problems of patients with CLD are prominent and deserve our attention and care. This study analyzed 320 patients with CLD who were hospitalized between January 2018 and January 2020. Questionnaire surveys were used to assess mental health status, including the Self‐Rating Anxiety Scale (SAS), Self‐Rating Depression Scale (SDS), and Symptom Checklist‐90 (SCL‐90). At the same time, basic data and potential related factors were collected. Data were analyzed using descriptive statistics and logistic regression. Among the 320 patients with CLD, 240 (75%) had mental health problems; among the total patients, education levels, occupations, course of disease, annual hospitalizations, complications, and nursing satisfaction were significantly different between the two groups ( p < .05). The education levels and occupations of the group without mental health problems were significantly different within the group ( p < .05). The SCL‐90 found that the four factors with the highest scores were anxiety (ANX: 33.3%), depression (DEPR: 20.4%), somatization (SOM: 12.9%), and sleep and diet (SD: 9.6%). Logistic regression analysis showed that education levels, course of disease, annual hospitalizations, complications, and nursing satisfaction levels were independent risk factors for the mental health of patients with CLD. Model fitness was checked using the Hosmer–Lemeshow test. The receiver operating characteristic (ROC) curve showed that the area under the curve was 0.84. Patients with CLD have prominent mental health problems and experience many risk factors. It is necessary to adopt individualized psychological interventions and care to improve the quality of life of these patients.